Factors Affecting Nurses’ Pain Management Practice in Neonatal Intensive Care Units - Tassaneeyarat, Sirinna; Deoisres, Wannee; Chaimongkol, Nujjaree (Journal of The Royal Thai Army Nurses, 2022)
This cross-sectional study aimed to examine the factors that effect on nurses’ pain management practice in hospitalized neonates in Thailand. The participants performed involving 118 neonatal nurses working in the Neonatal Intensive Care Units (NICUs) from general hospitals in Thailand by using multistage sampling. The instruments consisted of the Nurse’s Knowledge Regarding Pain Management in Neonates, the Nurse’s attitude Regarding Pain Management in Neonates, and the Nurses’ Pain Management Practice Questionnaire. The reliability of instruments were 0.70, 0.72, and 0.80 respectively. Data analyzed by using descriptive statistic and Multiple Regression Analysis. The results shown that most neonatal nurses had often providing a practice on procedural pain management in neonates. Nurse’s knowledge regarding pain management in neonates, nurse’s attitude regarding pain management in neonates, and experience of infant care together explained 40.9% of the total variance of nurses’ pain management practice in neonates. Knowledge distinctively acted as the most significant predictor of pain management practice (β = .435, p<.001), followed by attitude (β = .257, p = .001) and experience of infant care (β = .236, p<.01). These findings suggest that nurse administrators should promote nurses’ competencies by providing a mentoring system, create courses for neonatal pain management, and providing the guideline for neonatal pain management in their units.